Outcome of total laparoscopic hysterectomy in women with previous caesarean section - Neupane, Bhanubhakta; Karki, Gyanendra Man Singh; Pokharel, Hanoon P; Dahal, Prerana; Bhandari, Garima (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To assess the surgical outcome of total laparoscopic hysterectomy performed in women with previous caesarean section. Methods: This is a cross sectional analytical study conducted at Birat Medical College, Teaching Hospital from 1 May 2019 to 28 February 2020. One hundred thirty patients undergoing total laparoscopic hysterectomy were categorized in two groups with and without previous caesarean section. The data were entered into Microsoft Excel and analyzed by using statistical package for social studies (SPSS 23.0). Results: The overall complication rate was 3.87% (5/130) with 4.61% (3/65) in previous cesarean section and 3.07% (2/65) without it. Urinary tract injury was the common injury. Mean operating time was slightly higher in previous cesarean section but was not statistically significant. Conclusions: Total laparoscopic hysterectomy can be performed in patients with previous caesarean section without any significant increase in intraoperative and immediate postoperative complications. Keywords: adhesion, caesarean section, hysterectomy, laparoscopic